REVIEW PAPER QTL MAPPING FOR CROP IMPROVEMENT AGAINST ABIOTIC STRESSES IN - CEREALS H. M. Ahmad; Mahmood-ur-Rahman; F. Azeem; N. Tahir; M. S. Iqbal (Journal of Animal and Plant Sciences, 2018)
Quantitative trait loci (QTL) approach is the source for plant breeders to scrutinize the complex traits like drought, temperature, salinity stress tolerance, etc. into their components as they largely affect the crop productivity. Agricultural production can be enhanced by incorporating the tolerance against these stresses. In this review article, we will discuss the progress made by various researchers in the area of QTL mapping for the improvement of abiotic stress tolerance in cereals. The knowledge may be helpful for plant breeders to accelerate the release of abiotic stress resistant cultivars by reducing selection time of desirable traits and to incorporate the precise and accurate alleles in breeding programs. intensively used to find the precise location of the
Keywords: QTL mapping; abiotic stress; drought stress; salinity stress; heavy metal stress; heat stress.